Factors Influencing the Economic Results of Quarries - PITŘÍK, Jakub (GeoScience Engineering, 2023)
Human prosperity is closely linked to the availability of raw material resources, among other things. Despite enormous technological progress, we cannot dispense with mineral extraction. Since the mining industry still represents a key sector for society, striving for keeping abreast of the best practices, technologies, and knowledge available in the field is crucial. Benchmarking can serve this purpose, as it is already widely used in other industries. However, the question arises of what specific benchmarks are key for this field. The aim of this paper is, therefore, to highlight critical benchmarks relevant to monitoring and evaluating mining capacities. These have been identified by analysing the financial performance of specific mining operations. Keywords: Benchmarking; Discriminant analysis, Financial result; Quarrying.